Urgency of character building of students’ love of homeland through the historical teacher’ s role in state senior high school 4 of Kairatu, Ambon - Talapessy, Rostin; Kumalasari, Dyah; Salouw, Joniel Hendrik (ScienceRise: Pedagogical Education, 2020)
The purpose of this study is to know how many efforts the historical teachers done in state senior high school 4 Kairatu Ambon in building students’ love of homeland character through the historical subject by the qualitative approach. The data source in this research consists of primary and secondary data. The technique of data collecting used observation, interview, questionnaire and documentation. The technique of data analyzing in this research is conducted by four stages covering; 1) collecting, 2) data reduction, 3) data presentation, 4) making decision. The research founding indicates that there are three aspects, strived by the historical teacher of State Senior high school 4 kairatu in the effort of love of homeland character formation toward the students at school. Those aspects cover: discipline aspect, religious aspect and academic aspect. Discipline aspect covers controlling students to obligated attending the flag ceremony and anticipating the problem concerning with students’ lateness in coming school on time. The religious aspect concerns with worship implementation at school, and academic aspect covers: teacher make the policy concerning with students’ academic problem, such as students’ absence during class hours, smoking at the school environment, students have no respect toward teachers and other students, and so on